2014
DOI: 10.1016/j.jneumeth.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A unified framework and method for automatic neural spike identification

Abstract: Automatic identification of action potentials from one or more extracellular electrode recordings is generally achieved by clustering similar segments of the measured voltage trace, a method that fails (or requires substantial human intervention) for spikes whose waveforms overlap. We formulate the problem in terms of a simple probabilistic model, and develop a unified method to identify spike waveforms along with continuous-valued estimates of their arrival times, even in the presence of overlap. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(174 citation statements)
references
References 47 publications
2
172
0
Order By: Relevance
“…A simpler approach motivated by the model (9) and the ideal constraint set (14) is possible makingv n = x (1) n and τ n = x (2) n /x (1) n , but we found that (16) and (17) consistently provide smaller errors in our simulations. A possible explanation is the fact that the ideal constraint set is relaxed, as described in Section II-B, allowing solutions that do not strictly follow (14).…”
Section: Recovery Of Continuous Time Shifts and Amplitudesmentioning
confidence: 80%
See 2 more Smart Citations
“…A simpler approach motivated by the model (9) and the ideal constraint set (14) is possible makingv n = x (1) n and τ n = x (2) n /x (1) n , but we found that (16) and (17) consistently provide smaller errors in our simulations. A possible explanation is the fact that the ideal constraint set is relaxed, as described in Section II-B, allowing solutions that do not strictly follow (14).…”
Section: Recovery Of Continuous Time Shifts and Amplitudesmentioning
confidence: 80%
“…This encourages further investigations on practical problems where the problem of off-grid deviation is present. For instance, the Taylor and the Polar bases have been used, respectively, in neuron spike identification [1] and compressive sensing of frequency-sparse signals [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) ij=-ji=k (3) jk=-kj=i (4) ki=-ik=j (5) The quaternion can be represented in complex 22  matrices zw a+ib c+id H= = -c+id a-ib -w z       (6) where z and w are complex numbers, a , b , c , and d are real, and z is the complex conjugate of z .…”
Section: Quaternion Principle Component Analysismentioning
confidence: 99%
“…Yuan Yuan, and Chenhui Yang presented a robust and automatic spike detection and sorting system named the M-Sorter which was equipped with the multiple correlation of wavelet coefficients (MCWC) and a template matching classification [5]. Chaitanya Ekanadham presented a unified frame for automatic identification of neural spike, which used the Continuous Basis Pursuit (CBP) algorithm to classify spikes [6]. Quiroga presented a unsupervised classification method on the wavelet and superparamagnetic clustering [7].…”
Section: Introductionmentioning
confidence: 99%